Stationarity changes in long-run fossil resource prices: Evidence from persistence break testing - Aleksandar Zaklan; Jan Abrell; Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper considers the question of whether changes in persistence have occurred during the long-run evolution of U.S. prices of the non-renewable energy resources crude oil, natural gas and bituminous coal. Our main contribution is to allow for a structural break when testing for a break in persistence, thus disentangling the effect of a deterministic break from that of a stochastic break and advancing the existing literature on the persistence properties of non-renewable resource prices. The results clearly demonstrate the importance of specifying a structural break when testing for breaks in persistence, whereas our findings are robust to the exact date of the structural break. Our analysis yields that coal and natural gas prices are trend stationary throughout their evolution, while oil prices exhibit a break in persistence during the 1970s. The findings suggest that especially the coal market has remained fundamentals-driven, whereas for the oil market exogenous shocks have become dominant. Thus, our results are consequential for the treatment of energy resource prices in both causal analysis and forecasting.
Keywords: C12; C22; Q31; Q41; 330; non-renewable resource prices; primary energy; persistence; structural breaks